Sporadic and familial cases of aquagenic keratoderma - Nazik, Hulya; Nazik, Selcuk; Coban, Feride Gul; Demir, Betul (Specjalisci Dermatolodzy, 2016)
Background: Aquagenic keratoderma is a dermatosis characterized by transient whitish and transluscent hyperwrinkling after water exposure. The aim of the current report was to present a sporadic and familial cases of aquagenic keratoderma. Observation: Sporadic Case: A 38-year-old female patient presented with eruption in the right hand after exposure to water. The patient was placed on systemic acitretin therapy with the diagnosis of idiopathic acquired aquagenic keratoderma. No recurrence occurred during a 6-month follow-up period. Familial Cases: A 55-year-old male patient, who was engaged in fishery, presented to the outpatient clinics of the department of dermatology due towhitish vesicles in the palms of both hands. It was realized that the father, sister, and brother of the patient had similar complaints. The cases were thought to have familial aquagenic keratoderma; however acitretin therapy could not be initiated due to elevated alanine aminotransferase and triglyceride levels. Topical application of salicylic acid 10% and 10% urea containing lotions was effective but did not prevent recurrence. Conclusion: Systemic acitretin may be an effective agent in the treatment of aquagenic keratoderma, and topical application of 10% salicylic acid and 10% urea-containing lotion did not prevent recurrence.
Keywords: acitretin aquagenic keratoderma; retinoids; treatment